(untitled) (Bangladesh Journal of Agricultural Research, 2008)
Stability analysis was carried out for grain yield and its components in six HYV boro rice varieties across five different planting dates. Highly significant genotypes, environment and G Ã E interaction were observed for all the traits. Non-linear component (pooled deviation) was found highly significant for grain yield and its components, while linear components (variety Ã planting time) were only significant for plant height. BRRI dhan27, BRRI dhan29, and BRRI dhan36 were found suitable for favourable environments. Among the varieties, BRRI dhan29 was the top yielder followed by BRRI dhan27 and BRRI dhan36. 30 December and 15 January were suitable planting time for these varieties in northern area, especially in Rangpur. For better production, transplanting must be completed within December to mid January. Bangladesh J. Agril. Res. 32(4): 559-564